Pak1 and Pak2 are activated in recurrent respiratory papillomas, contributing to one pathway of Rac1-mediated COX-2 expression - Wu, Rong (2010)
Recurrent respiratory papillomas are pre-malignant tumors of the airway caused by human papillomaviruses (HPVs), primarily types 6 and 11. We had reported that respiratory papillomas overexpress the epidermal growth factor receptor (EGFR), the small GTPase Rac1 and cyclooxygenase-2 (COX-2), and have enhanced Nuclear Factor-κB (NFκB) activation with decreased levels of IκB-β but not IκB-α. We also showed that EGFR-activated Rac1 mediates expression of COX-2 through activation of p38 mitogen activated protein kinase. We have now asked whether the p21-activated kinases Pak 1 or Pak2 mediate activation of p38 by Rac1 in papilloma cells. Pak1 and Pak2 were constitutively activated in vivo in papilloma tissue compared to normal epithelium, and Rac1 siRNA reduced the level of both phospho-Pak1 and phospho-Pak2 in cultured papilloma cells. Reduction in Pak1 and Pak2 with siRNA decreased COX-2 expression in papilloma cells, increased levels of IκB-Iβ and reduced nuclear localization of NF-κB, but had no effect on p38 phosphorylation. Our studies suggest that Rac1→ Pak1/Pak2→ NFκB is a separate pathway that contributes to the expression of COX-2 in HPV-induced papillomas independently of the previously described Rac1→ p38 → COX-2 pathway.